A Brief History of the Royal College of Surgeons of Edinburgh (Res Medica, 2014)
The Royal College of Surgeons of Edinburgh has enjoyed a continuous existence as a corporate body since 1505. It may justly claim to be one of the oldest surgical corporations in the world. The Barber Surgeons of Edinburgh were formally incorporated as a Craft Guild of the city and this recognition is embodied in the Seal of Cause or Charter of Privileges which was granted to the Barber Surgeons by the Town Council of Edinburgh on 1st July 1505. The Seal of Cause is a remarkable document. It clearly established the role of the Incorporation of Barber Surgeons as a body concerned with the maintenance and promotion of the highest standards of surgical practice and this remains the prime purpose of the great international surgical brotherhood of the Royal College which has developed from the Incorporation. The Seal of Cause conferred various privileges upon the Incorporation, including the exclusive right of its members to practise surgery in Edinburgh and surrounding districts, but in return for these privileges, it imposed certain crucially important duties and obligations. The most important of these, which remains entirely appropriate to this day, is stated very clearly in the Seal of Cause, “that na maner of persoun occupie nor vse ony poyntis of our said craftis of Surregenie ... bott gif he be first frieman and burges of the samyn, and that he be worthy and expert in all the poyntis belangand the saidis craftis diligentlie and avysitly examinit and admittit be the maisters of the said mcraft ... that he knaw anotamell, nature and complexion of euery member humanis bodie, and inlykewayes he knaw all the vaynis of the samyn ... for euery man aucht to knaw the nature and substance of euery thing that he werkis, or ellis he is negligent.” From its earliest origins the College has been an examining body principally concerned with the setting and maintenance of professional standards. Another vitally important obligation laid upon the Barber Surgeons was that of ensuring that all who practise the craft should be able to read and write and this literacy requirement is the earliest of any comparable professional body.